Pathological changes and oxidative stress of the HPG axis in hypothyroid rat. (11th August 2021) - Wang, Lu; He, Wen; Xu, Xiaoyu; Qi, Lingbin; Lv, Bo; Qin, Jiaying; Xue, Zhigang; Xue, Jinfeng
Abstract : Hypothyroidism is a common endocrine disease caused by a deficiency of thyroid hormones, which could affect the hypothalamus–pituitary–gonadal (HPG) axis and cause additional severe fertility problems. However, the pathogenesis of abnormal reproductive capacity caused by hypothyroidism and whether there are differences between females and males need more study. Here, we constructed a prolonged neonatal hypothyroid rat model using 6-propyl-2-thiouracil (PTU). H&E staining and RNA-sequencing were performed to detect histopathological and transcriptome changes. Our results indicated that the numbers of ventromedial hypothalamus nuclei were increased, and the number of pituitary chromophobes was sharply increased, whereas the proportion of pituitary acidophils and pituitary basophils were obviously reduced. The differentially expressed genes of the HPG axis organs were identified, and different tissues shared similar steroid hormone and oxidative stress-related terms in gene ontology analysis. Weighted gene co-expression network analysis (WGCNA) and differential expression analysis indicated oxidative stress, and apoptosis-related genes were more enriched in male hypothyroid pituitaries, whereas the serum levels of growth hormone, follicle-stimulating hormone, and luteinizing hormone that were detected by ELISA were also reduced more in male hypothyroid rats, suggesting that prolonged neonatal hypothyroidism may have a more significant impact on male pituitaries. Moreover, the multi-organ oxidative stress in hypothyroid rats was confirmed by the higher expression of oxidative stress-related genes, such as the Txnip . The increased level of oxidative stress may have contributed to the histopathological and transcriptome changes of HPG axis organs in the prolonged neonatal hypothyroidism rats, especially in male pituitaries.